Adaptive adjustment to the needs of families caring for children and adolescents with physical disabilities in north-eastern Tanzania: a grounded-theory study - Elia Asanterabi Swai; Haleluya Imanueli Moshi; Sia Emmanueli Msuya; Marie Lindkvist; Ann Sörlin; Klas Göran Sahlen (Taylor & Francis Group, 2024)
Background Family interactions, which are always multi-faceted, are complicated further by family members with disabilities. In resource-poor settings, policies and programmes that address the needs of and challenges faced by families are often inaccessible or unavailable. Approximately 13% of the families in Tanzania have at least one member with a disability, yet family-centred research on caring for disabled children and adolescents is scarce in this context. Objective The aim is to explore the needs and challenges faced by families that care for children and adolescents with physical disabilities in the Kilimanjaro Region of north-eastern Tanzania. Methods This qualitative study had a constructivist grounded-theory design. In-depth interviews, using a semi-structured interview guide based on the social-capital framework, were conducted with 12 female participants aged between 24 and 80. A conceptual model of family needs, inspired by Maslow's hierarchy of needs, informed the analysis. Results Challenging needs were grouped into five categories, which were linked to Maslow's hierarchy of needs and related to the central concept of 'adaptive adjustment': (1) 'barely surviving'; (2) 'safety needs in jeopardy'; (3) 'sociocultural protection'; (4) 'self-esteem far beyond reach', and (5) 'dreaming of self-actualisation'. Conclusion Families caring for children and adolescents with physical disabilities in north-eastern Tanzania have needs that extend beyond the available and accessible resources. Families can adjust and adapt by avoiding certain situations, accepting the reality of their circumstances and exploring alternative ways of coping. A sustainable support system, including social networks, is essential for meeting basic needs and ensuring safety.